(untitled) (Research, Society and Development, 2020)
The study of work related to the environment, which takes into consideration the work environment and who does it (the workers) is the basis for ergonomics, it is used to determine how to design or adapt the work environment to the worker in order to avoid health problems and increase productivity. The present work was carried out with the objective to evaluate if the structural conditions of a ceramics, located in the municipality of Campo do Brito, Sergipe, were in agreement with the regulatory laws and principles of ergonomics to carry out the activities of the employees. The evaluations were carried out with the completion of the questionnaires: Bipolar / QPB and the Body Diagram. Twenty employees were interviewed and visited during working hours. The data collection allowed a survey of some common errors in the execution of the tasks that can lead to the unnecessary physical wear and tear of the employees during the repetitive work. Therefore, the results of this study allow us to assist in the elaboration of a program of efficiency improvements and injury prevention in the work environment.